Evaluación de la eficiencia de herbicidas para el control de malezas en plantación de Pinus radiata D. Don, en el sector Itulcachi, parroquia Pifo, Provincia de Pichincha, año 2019. - Peña Macias, Damian Enrique (2019)
The research project was carried out at the Itulcahi farm, in the sector with the same name, Pifo parish, Pichincha province. The plantations of P. radiata in the place, like other forest plantations suffer from the presence of weeds, so it compromises the development and growth of the species, especially in its first years of life, so this study made the application of herbicides for the eradication of these undesirable species. The objectives of the present investigation were to identify the weed species in the study area, determine the most effective herbicide and carry out an economic analysis among the chemical products, carrying it out in the months of July to October of this year. Prior to the application of the products, the quantification of weeds in a quadrant of 0.50 m2 was carried out and the collection and identification of existing weed species in the study area through guides and manuals acquired in the UTEQ herbarium. A total of 30 species were identified, observing that Hydrocotyle bonplandii, Dalea coerulea, Desmodium molliculum and Pennisetum clandestinum were the most abundant weeds within the trial, on the other hand, the diversity index showed 26 species. Of the 6 herbicides used, including the Anfino, Merlin, Verdic, Rambo, Truper and Glifopac, the most efficient in weed control was Rambo with 75.2% having as active ingredient Tryclopyr. Mild symptoms were observed between treatments, because the toxicity of the products against pine was low, so there were no statistical differences. The cost analysis showed that the chemicals applied are around $ 27.02 to $ 340.07 per hectare. Keywords: Weeds, herbicides, toxicity, pine.